2004
DOI: 10.1590/s0004-282x2004000100025
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome in the course of dengue: case report

Abstract: -This case report describes the findings of a 45-year-old white woman from Brazil, who developed myalgia, fever and macular rash. She was diagnosed as having dengue, based on clinical manifestations and specific IgM titers. One week after the first symptoms of dengue, the patient developed muscle weakness, followed by tetraplegia with areflexia, and respiratory insufficiency. The electromyography had evidence of demyelinating neuropathy and the cerebrospinal fluid showed albuminocytologic dissociation. These n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 7 publications
0
37
0
2
Order By: Relevance
“…Neurological symptoms developed between four to nineteen days after the onset of dengue picture. All of them presented tetraparesis and, except for the case described by Santos et al 16 , had good recovery. The infection was suspected and confirmed in all of them, but only in one case the immunological test to dengue in the CSF was done 14 , and it was negative.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Neurological symptoms developed between four to nineteen days after the onset of dengue picture. All of them presented tetraparesis and, except for the case described by Santos et al 16 , had good recovery. The infection was suspected and confirmed in all of them, but only in one case the immunological test to dengue in the CSF was done 14 , and it was negative.…”
Section: Discussionmentioning
confidence: 82%
“…Guillain Barré syndrome has been described by isolated reports. In our literature revision we found seven cases reports of GBS associated to dengue infection [13][14][15][16][17][18] . There were three children and six adults, ages ranging from one and half to 46 years old.…”
Section: Discussionmentioning
confidence: 99%
“…They also observed that potassium supplementation resulted in rapid improvement of symptoms. Santos et al [6] reported GB syndrome in the course of dengue. The clinical profile of dengue is changing, and the neurological manifestations are reported more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Widodo et al [2] observed prevalence of hypokalemia in 23% (n = 105) of the hospitalised patients with infectious disease and Kalita et al studied 16 patients with dengue fever with quadriparesis, in seven, the pure motor quadriparesis was due to myositis. [6] Hypokalemia in association with infectious diseases, particularly in dengue fever, has been reported. Hypokalemic paralysis secondary to chikungunya fever has also been documented.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report on three cases in New Caledonia showed findings similar to those reported here 3 , while fatal cases have recently been described in India 4 and Pakistan 5 . In Brazil, which has been an endemic region for dengue fever for over two decades, very few cases of associated GBS have been reported 6,7,8,9 . These authors believe that GBS in association with dengue fever may be underdiagnosed, even in endemic areas.…”
mentioning
confidence: 99%